New Generation Software-Only Architecture for Gaze-Contingent Eyetracking Experimentation - I.Y. Zherdev (Экспериментальная психология)
The author shares 10+ years of experience in eyetracking research. Most crucial technicalities are described, different programming approaches are discussed. Network Time Protocol [19] application to data stream synchronization is reviewed separately, which renders phototransistor on-screen sensors partially redundant in some of psychophysics disciplines (known as TTL hardware).